A Reality of the Digital Transformation of Banks in Africa: Banking Services through Smart Phones as a Model - روفية ضيف (Finance and Business Economies Review, 2023)
The study aims to analyze the status of mobile financial services in African banks during the third millennium. It utilized digital channels to provide banking services that save time, effort, cost, and facilitate operations and money transfers. This has led to increased customer satisfaction and loyalty. The study concludes that the mobile services market in Africa is promising, driven by the young population and the widespread availability of electronic communication networks. It has provided significant opportunities in the digital transformation era, particularly among low-income segments of society. The local electronic payment market has experienced a 20% annual revenue growth, surpassing 24 billion in 2020, serving as a driving force for innovative and sustainable growth. However, the study also indicates that service availability is uneven across markets, despite the continuous and increasing demand for mobile services.